Vlog Portfolio as a Technique of Speaking Assessment in Islamic Boarding School - Farid Noor Romadlon; Balwas, Rasheed (Universitas PGRI Semarang, 2024)
English holds great significance in Indonesia, particularly within Islamic boarding schools (Pesantren). Despite its introduction in primary schools, surveys reveal that the majority of graduates face common communication issues, such as inadequate speaking abilities and a dearth of interaction skills. Communicating in English for a second language speaker is a difficult task due to a variety of reasons associated with the fear of speaking English, such as language anxiety, restricted vocabulary, and a lack of exposure to the language, as argued by the researcher. This paper aims to offer an elaboration of vlog portfolio as a technique in teaching and assessing speaking in Islamic boarding schools. A vlog portfolio can be an alternate strategy for students in promoting their progress of speaking performance